Pemberdayaan Perekonomian Desa Melalui Penguatan Potensi Sumber Daya di Desa Licin Kecamatan Cimalaka Kabupaten Sumedang - M. Samsuri; Euis Eti Rohaeti; Heris Hendriana; Dinno Mulyono (UNISBA Press, 2024)
Abstract. Economic empowerment in villages can be done by looking at the problems, potential and needs of the village community. Licin Village, which is in Cimalaka District, Regency Sumedang, has a number of potentials to be developed as an effort to empower the economy in the village. Through the implementation of activities carried out by ten students of the Type 3 Independent Mutual Cooperation Village Depelopment (PTMGRMD), College program from IKIP Siliwangi and Sebelas April University, economic empowerment in Livin village was carried out by organizing Ciburial Springs tourism, increasing kancra fish cultivation, improving the quality of human resources through handling stunting and increasing literacy in extreme poor communities. From the results of these activities, the results showed that the implementation of these activities was effective in increasing economic empowerment in Licin Village. Abstrak. Pemberdayaan ekonomi di desa bisa dilakukan dengan melihat permasalahan, potensi dan kebutuhan masyarakat desanya. Desa Licin yang berada di Kecamatan Cimalaka Kabupaten Sumedang memiliki sejumlah potensi untuk dikembangkan sebagai upaya memberdayakan perekonomian di desa tersebut. Melalui implementasi kegiatan yang dilakukan oleh sepuluh orang mahasiswa program Perguruan Tinggi Mandiri Gotong Royong Membangun Desa (PTMGRMD) Tipe 3 dari IKIP Siliwangi dan Universitas Sebelas April, maka pemberdayaan ekonomi di desa Livin dilakukan dengan cara penataan wisata Mata air Ciburial, peningkatan budidaya ikan kancra, peningkatan kualitas sumber daya manusianya melalui penanganan stunting dan peningkatan Literasi masyarakat miskin ekstrim. Dari hasil kegiatan tersebut diperoleh hasil bahwa implementasi kegiatan tersebut efektif dalam meningkatan pemberdayaan perekonomian di Desa Licin.